2008
DOI: 10.1007/s10800-008-9512-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Teflon loading in the gas diffusion layer of PBI-based PEM fuel cells

Abstract: The influence of the PTFE content in commercial Toray graphite paper gas diffusion layer (GDL) on the performance of a PBI-based polymer electrolyte membrane fuel cell (PEMFC) has been studied. These materials have been characterised by evaluating the porosity, pore size distribution, SEM micrographs, hydrophobicity, air permeability and electrical resistance. Fuel cell results show that the lower the Teflon content, the better the cell performance and the lower the losses when oxygen was replaced by air. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 50 publications
(66 reference statements)
7
92
0
Order By: Relevance
“…Table 7 shows some types of GDLs used in HT-PEMFCs in literature. To the authors knowledge, only one paper has been found in the literature on GDLs for high temperature, i.e., Lobato et al [92] which studied the effect of PTFE loading in the GDL on PBI-based PEM fuel cell. It was reported that lower PTFE loading results in a higher cell performance but it has a negative effect on the mechanical properties of the GDL and a 10% PTFE loading is suggested as an optimum value for HT PEM.…”
Section: Gas Diffusion Layer and Flow Field Platesmentioning
confidence: 99%
“…Table 7 shows some types of GDLs used in HT-PEMFCs in literature. To the authors knowledge, only one paper has been found in the literature on GDLs for high temperature, i.e., Lobato et al [92] which studied the effect of PTFE loading in the GDL on PBI-based PEM fuel cell. It was reported that lower PTFE loading results in a higher cell performance but it has a negative effect on the mechanical properties of the GDL and a 10% PTFE loading is suggested as an optimum value for HT PEM.…”
Section: Gas Diffusion Layer and Flow Field Platesmentioning
confidence: 99%
“…Previous work with the GDL has focused on hydrophobic treatments with Teflon and adding an MPL to minimize water intrusion into the GDL [7,13,15,17,[27][28][29][30][31][32][33][34]. The work of Kimball et al [37] coupled with the GDL characterization presented here show that the flow of water from the catalyst layer through the GDL is a component of the fuel cell design.…”
Section: Implications For Fuel Cell Designmentioning
confidence: 84%
“…A common focus is adding Teflon to the carbon fiber GDL materials to limit flooding [13,15,17,[27][28][29]. Other researchers have also considered the potential to control GDL saturation using a hydrophobic microporous layer (MPL) between the catalyst layer and the GDL [7,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the own polymeric electrolyte has got also an important role, since the solubility of the gas in it is highly dependant on the cell operation conditions (Liu et al, 2006). In the case of H 3 PO 4 doped PBI-based high temperature PEMFC, compared to traditional Nafion ® -based PEMFC, mass transport becomes slightly simpler since all the species are in vapour state, and therefore, flooding problems do not appear (Lobato et al, 2008b). However, this does not imply that mass transport processes are not important in terms of cell performance.…”
Section: Mass Transport In Polymer Electrolyte Membranes Fuel Cellsmentioning
confidence: 99%
“…Generally, this carbon support is wet-proofed with a certain amount of Teflon, which assists in an effective water management, and provides a pathway for the access of the reactant gases when massive amounts of water are being generated in the cathode (Park et al, 2004). Also, this amount of Teflon helps to keep the mechanical integrity of the gas diffusion layer during the hot pressing procedure used to prepare the membrane-electrodeassembly (MEA) (Lobato et al, 2008b). In some cases, a second layer is incorporated to the GDL design, the microporous layer.…”
Section: The Role Of the Gas Diffusion Layer In High Temperature Pemfcmentioning
confidence: 99%